2019
DOI: 10.1029/2019jc015027
|View full text |Cite
|
Sign up to set email alerts
|

Improving Surface Current Estimation From Geostationary Ocean Color Imager Using Tidal Ellipse and Angular Limitation

Abstract: Sea surface currents (SSCs) in coastal regions can be mapped from successive optical images observed by satellite. We implemented the maximum cross‐correlation (MCC) algorithm to Geostationary Ocean Color Imager‐derived total suspended matter in the East China Sea in this study. We developed a new data filtering method to improve the accuracy of SSC vector sequence using estimated tidal ellipse. The proposed method eliminated spurious vectors by considering direction order and suitable angular limitation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies suggested the existence of many unrealistic velocity vectors in MCCderived surface currents [2,7]. Great efforts are made to eliminate erroneous vectors using various techniques [6,9,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested the existence of many unrealistic velocity vectors in MCCderived surface currents [2,7]. Great efforts are made to eliminate erroneous vectors using various techniques [6,9,30].…”
Section: Discussionmentioning
confidence: 99%
“…The MCC method is commonly used to estimate hourly total surface currents from the sequential tracer images [4,6,7,10,12,13]. Briefly, a sub-source box in an initial image is cross-correlated with the same size box in a subsequent image, searching for the most likely location in the second image by the maximum cross-correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations